TP53 mutation is frequently associated with CTNNB1 mutation or MYCN amplification and is compatible with long-term survival in medulloblastoma - Pfaff, Elke; Remke, Marc; Sturm, Dominik; Benner, Axel; Witt, Hendrik; Milde, Till; Bueren, André von; Wittmann, Andrea; Schöttler, Anna; Jorch, Norbert; Graf, Norbert; Kulozik, Andreas; et al. (Journal of clinical oncology, 2010)
Purpose - - The role of TP53 mutations in the tumorigenesis of sporadic medulloblastoma (MB) and the value of TP53 mutation status as a prognostic marker are not yet definitely elucidated. A recent report identified TP53 mutations in MB as an adverse prognostic marker. Hence, the current study was conducted to validate the prognostic role of TP53 mutation in MB and to understand its contribution to tumorigenesis. - - Methods - - A comprehensive genetic analysis of 310 MB samples was performed by screening for TP53 mutations and further relating the TP53 mutation status to p53 immunostaining, cytogenetic aberrations, and clinical variables. - - Results - - Mutation analysis of TP53 revealed mutations in 21 (6.8%) of 310 samples. Germline TP53 mutations were found in two patients with a history suggestive of a hereditary cancer syndrome. TP53 mutation status was not associated with unfavorable prognosis (P = .63) and was not linked to 17p allelic loss but was over-represented in the prognostically favorable WNT subgroup of MB as defined by CTNNB1 mutation (seven of 35 TP53-mutated tumors v 14 of 271 TP53 wild-type tumors; P = .005) and in tumors carrying high-level MYCN amplification (seven of 21 TP53-mutated tumors v 14 of 282 TP53 wild-type tumors; P = .001). - - Conclusion - - The contradictory results in the recent literature concerning the prognostic value of TP53 mutation might be explained by different frequencies of WNT MBs, different frequencies of patients with Li-Fraumeni syndrome, and different cumulative doses of alkylating drugs applied in these studies.